ANALISIS CITRA MEREK (BRAND IMAGE) PADA KFC CABANG SUDIRMAN PEKANBARU - Amalia Hasanah; Eka Komalasari (VALUTA, 2021)
This study aims to analyze the analysis of the brand image (brand image) at KFC Sudirman Pekanbaru branch. The indicators in this study are company image, user image and product image. The type of research used is descriptive, namely prioritizing questionnaires as a data collection tool, of the objectivity of the existence of research objectives at the location. and the method used by the writer is quantitative method. There is a population and sample in this study, namely visitors who came to the KFC, reached 44 people. The sampling technique used in this research is incidental sampling, which is the determination of the sample by chance, that is, anyone who happens to meet the researcher can be used as a sample. data collection techniques used questionnaires, interviews, observation and documentation. data analysis technique used is descriptive analysis of quantitative data, namely describing the data through numbers and the acquisition of data collection by giving weights or scores on the questionnaire. Based on this analysis technique, the researcher assesses and the brand image for indicators of corporate image, user image and product image are categorized as "very good"